METODE TECHNOLOGY ACCEPTANCE MODEL (TAM) PADA SISTEM INFORMASI TUGAS AKHIR PROGRAM STUDI ILMU KOMPUTER UNIVERSITAS NUSA CENDANA - Umanailo, Ali; Rumlaklak, Nelci D.; Widiastuti, Tiwuk (Jurnal Inovatif, 2022)
The absence of an information system related to research results in the Computer Science study program, Faculty of Science and Engineering, Nusa Cendana University resulted in the limited provision of research information services in this study program because the scope of delivering information to the wider community was limited. In this research, planning, design and development of a research information system is carried out which will later be used to publish research results in order to provide a source of knowledge about research in study programs to the wider community. The Waterfall system development method uses a Descriptive Analysis approach and refers to five perceptions. The Technology Acceptance Model (TAM) method is used to measure user satisfaction with the system being built. The test was carried out using 59 test data collected directly from prospective students using the system. The test results got a satisfactory value with each perception value, namely: Perceived Ease Of Use of 82.18%, Perceived Usefulness of 81.69%, Attitude Toward Using of 76.90%, Behavioral Intention To Use of 79% and Actual Technology Usage is 81% with an average overall perception percentage of 79.98% and is in the good/high category. Keywords: Information System, Study Program, Waterfall, Technology Acceptance Model (TAM).